Discovery of Piperidine‐Linked Pyridine Analogues as Potent Non‐nucleoside HIV‐1 Reverse Transcriptase Inhibitors. Issue 7 (3rd May 2013) - Chen, Xuwang; Li, Yuanyuan; Ding, Shufang; Balzarini, Jan; Pannecouque, Christophe; De Clercq, Erik; Liu, Huiqing; Liu, Xinyong
Abstract In our continued efforts to discover more active and less toxic HIV‐1 non‐nucleoside reverse transcriptase inhibitors, we recently designed a novel series of piperidine‐linked pyridine analogues on the basis of diarylpyrimidine derivatives, among which two drugs—etravirine and rilpivirine—are approved for use by the US FDA. The title compounds were evaluated for activity against wild‐type and resistant mutant strains of HIV‐1 as well as HIV‐2 in MT‐4 cells. The highly potent compound BD‐c1 (EC50=10 nM, CC50≥146 μM, SI≥14 126) displays lower cytotoxicity and higher selectivity than etravirine (EC50=2.2 nM, CC50=28 μM, SI=12 884) against wild‐type HIV‐1. Compound BD‐e2 (EC50=5.1 nM) shows greater antiviral efficacy against wild‐type HIV‐1 than do the four reference drugs nevirapine, delavirdine, efavirenz, and zidovudine. Many compounds were also found to be active against the frequently observed drug‐resistant double mutant (K103N+Y181C) HIV‐1 strain. Herein we report the design, synthesis, anti‐HIV evaluation, preliminary structure–activity relationships, and molecular simulations of novel piperidine‐linked pyridine analogues.